Analisis Peranan Handling Cargo Terhadap Proses Bongkar Muat di PT. Terminal Teluk Lamong - Faradita Ayu Anggraini; Intan Sianturi; Prima Yudha Yudianto; Rizqi Aini Rakhman (Pusat riset dan Inovasi Nasional, 2025)
The role of Cargo Handling on the Loading and Unloading Process at PT Terminal Teluk Lamong is very important for the loading and unloading process at the port. This research aims to identify various technical and non technical obstacles in the operation of cargo handling equipment such as ASC, forklift, and reach stacker. The interview results showed that there are four main factors that become obstacles in the loading and unloading process, namely machines, methods, facilities, and manpower. Further analysis using fishbone diagrams reinforced these findings by outlining the causes of each factor, ranging from machine interference, wrong container placement methods, limited technological facilities such as Container Scanner Reader (CSR), to the driver’s lack of understanding of the automation system. Quantitatively, the efficiency of cargo handling was evaluated through the 2023 container throughput, which showed a positive trend with a significant increase in load activity, especially in October which recorded the highest number of 39.106 Boxes. The analysis concluded that although there are various obstacles in cargo handling practices, the system implemented by PT Terminal Teluk Lamong has generally been able to improve the efficiency of the loading and unloading process, as evidenced by the volume of container handling.